PHILOSOPHICAL AND LEGAL ASPECTS OF THE DEVELOPMENT OF LEGAL CULTURES - Yuriichuk, Olena (SUPREMANCE OF LAW, 2016)
The article deals with the categorical status of legal culture in the context of the philosophy of law, in particular, through the axiological approach as the most justified and meaningful, which provides a reflection of the universal values combination of the general culture with law. The tendencies towards the formation of the global integration of legal cultures, as well as their dialogue, and non-conflict of coexistence are emphasized. Four main philosophical and legal aspects of the legal cultures’ development are suggested, and their author’s definition is given. The author believes, it is important to take into account the following: the historical legal opinion, the emphasis on the values of law and culture, the consideration of historical memory during the practical application of legal cultures, as well as positive and tolerant attitude to existing internal differences, and understanding the importance of legal cultures’ dialogue.